2012
DOI: 10.1007/s00267-012-9919-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing Exclusion on Soil Properties and on Ecosystem Carbon and Nitrogen Storage in a Sandy Rangeland of Inner Mongolia, Northern China

Abstract: The Horqin sandy rangeland of northern China is a seriously desertified region with a fragile ecology. The sandy alluvial and aeolian sediments have a coarse texture and loose structure and are therefore vulnerable to damage caused by grazing animals and wind erosion. We investigated whether grazing exclusion could enhance ecosystem carbon (C) and nitrogen (N) storage and thereby improve overall soil quality. We compared soil properties, C and N storage in biomass (aboveground and below-ground), and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 40 publications
6
34
2
4
Order By: Relevance
“…Our study showed that the 6-year grazing exclusion had resulted in a significant recovery in vegetation with higher aboveground biomass, but a lower soil bulk density and pH value, which are consistent with earlier researches (Wu et al, 2009;Chen et al, 2012). The reduced perturbation had a direct effect on the aboveground biomass, demonstrating that grazing exclusion is an effective practice to improve vegetation productivity in degraded grassland (Tanentzap et al, 2009;Zhou et al, 2011).…”
Section: Effects Of Grazing Exclusion On Vegetation and Soil Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that the 6-year grazing exclusion had resulted in a significant recovery in vegetation with higher aboveground biomass, but a lower soil bulk density and pH value, which are consistent with earlier researches (Wu et al, 2009;Chen et al, 2012). The reduced perturbation had a direct effect on the aboveground biomass, demonstrating that grazing exclusion is an effective practice to improve vegetation productivity in degraded grassland (Tanentzap et al, 2009;Zhou et al, 2011).…”
Section: Effects Of Grazing Exclusion On Vegetation and Soil Propertiessupporting
confidence: 90%
“…These differences may partly due to whether grazing pressure exceeds carrying capacity of a site and whether it is sufficiently far beyond that capacity to reach the ecological threshold (Sasaki et al, 2011). Additionally, the discrepancies in duration of exclosure, climatic conditions, original and post-grazing vegetation, soil properties from different studies were also found to be the causes for the inconsistent results (Reeder et al, 2004;Chen et al, 2012;Medina-Roldan et al, 2012).…”
Section: Effects Of Grazing Exclusion On Vegetation and Soil Propertiesmentioning
confidence: 99%
“…This result was not consistent with the results from the Imam Kandi Rangelands, Iran (Mofidi et al, 2013), and in the sandy rangeland of Inner Mongolia, northern China (Li et al, 2011;Chen et al, 2012), in which grazing exclusion led to greater fine soil particle content and lower coarse sand content due to an increased ability of vegetation to prevent soil erosion and trap windblown fine particles H. Wen et al, 2013).…”
Section: Effect Of Grazing Exclusion On Soil Propertiescontrasting
confidence: 57%
“…F value P value F value P value F value P value F value P value F value P value BD Grazing exclusion substantially improved soil N availability in the temperate steppe in northern China, which suggests that there are positive effects of ecological restoration on soil N availability (Wang et al, 2010;Chen et al, 2012). However, this improvement was not found in alpine grasslands with ecological restoration by grazing exclusion (Fig.…”
Section: Soil Propertiesmentioning
confidence: 95%
“…Meanwhile, the maintenance of heterogeneous vegetation and associated topsoil structures is essential for the accumulation of SOC in semi-arid grassland ecosystems [34]. Increases in SOC resulted in decreased soil erosion by wind in this region due to increased vegetation cover, which enable nutrients to easily fix to the soil surface after livestock exclusion [35]. Another reason was that grazing cessation enhanced the soil aggregation as the physical protection of SOC [36].…”
Section: Effect Of Grazing Exclusion On Vegetation Characteristics Anmentioning
confidence: 99%